Impacts of bulk density and water content on the tire-soil contact area of agricultural field vehicles - Davi de Farias Thorpe; Mário Monteiro Rolim; Elvira Maria Reges Pedrosa; Djalma Eusébio Simões Neto; Roberta Queiroz Cavalcanti; Renato Paiva de Lima (Acta Scientiarum. Agronomy, 2024)
We tested the hypothesis that the increase in soil stiffness, induced by variations in bulk density and water content at the tire-soil contact interface, causes a reduction in the contact area. For this, we examined the contact area from different tire-ground contact scenarios and compared the measurements and simulations using a contact area description model. Front and rear tractor tires were used for the measurement of the contact area under tilled soil, sugarcane field, unpaved road, and paved ground scenarios, which induced different bulk densities and water content levels. The results revealed that soil stiffness reduced the tire-soil contact area. The tire-soil contact area increased as the water content increased and the bulk density was reduced. For the front tractor tire, the theoretical contact area was similar to the values found for tilled soil, but there was a large difference between the measurements (2,200 cm2, for the tilled soil) and the theoretical estimates (3,100 cm2) for the rear tractor tire (likely induced by tire dimensions). Our results suggest that increases in soil stiffness reduce the tire-soil contact area. The higher the soil bulk density and the lower the soil moisture, the lower the contact area. The results also revealed that the tire tractor tread might reduce the contact at the hard surface, making the shape of the contact area more geometrically irregular and different from those predicted by models using regular geometry (e.g., cycles, ellipses, or rectangles). This study suggests that two-body (soil and tire) contact models for deformable surfaces should be used in future tire-soil contact models of agricultural field vehicles.